Village Archives Management: The Foundation of Organizational Effectiveness Towards Good Governance - Dwi Astarani Aslindar; Bambang Triyono; Ahmad Nasori (Administratio, 2025)
Archive management plays an important role in public administration services implemented by government agencies, both central and regional, especially in meeting the needs of the community. Effective archive management can improve organizational efficiency, which ultimately supports the principles of good governance. In the villages of Jatilawang District, archive management has not been fully optimized, resulting in public administration services not meeting community expectations. This study aims to analyze archive governance, the challenges faced, and their impact on the effectiveness of organizational work. In the long term, this study is expected to contribute to the development of administrative management science, especially in maintaining organized archives to support village development towards good governance. This study uses a mixed method approach, data collection through observation, interviews, and questionnaires. The findings show that although the villages in Jatilawang District have implemented an archiving process from recording to disposal, these villages have not fully complied with existing regulations due to certain constraints. This has an impact on the efficiency of the organization in providing public services, because archive management has a direct impact on organizational performance.